Mentor-mentee as a strategy to increase willingness to communicate among student leaders : a case study - Farhana Diana Deris; Norhayati Hasan; Noorsidi Aizuddin Mat Noor (Penerbit Universiti Kebangsaan Malaysia, 2021)
Effective leadership and effective communication are closely intertwined; leaders need to be skilled communicators in order to lead effectively. Nevertheless, past studies indicated that even among student leaders, their willingness to communicate (WTC) varies and is not always at desirable levels. Given that students with higher levels of WTC have a greater chance of improving their communication skills, there is a need to examine how it can be enhanced. This study aims to provide insights into WTC in the context of a sustained leadership and communication club where 24 student leaders participated as members. In particular, the paper will delve into the participants’ WTC levels and will discuss the perceived factors influencing their willingness to communicate. Using a case study research design with mixed-method approach, questionnaires, interviews and observations were used to gather data. The results revealed a significant growth in the participants’ WTC after they have participated in the club, with mentor-mentee strategy as a core factor contributing to the increased WTC. The findings suggested that mentorship in the club was a two-way street, involving mutual and reciprocal action and obligation, with the mentor playing a more dominant role, while the mentees take ownership of their growth and development. In addition to that, other affective factors such as motivation, self-confidence and anxiety were found to influence WTC. Grounded on the findings, a mentor-mentee model that explicates the constructs and components contributing to the perceived increased WTC will be presented.